Intellectuals in revolutionary China, 1921-1949 : leaders, heroes and sophisticates - Ip, Hung-yok, 1961- (Chinese worlds., 2005)
"In Intellectuals in Revolutionary China, 1921-1949 Hung-yok Ip examines how Communist intellectuals in China during the revolutionary period (1921-1949) constructed and presented identities for themselves. She looks at how they narrated their place in the revolution and how these identities later allowed them to claim to be the deserving elite of a revolution that sought to liberate the oppressed and bring about a better society. Not only does this book make a contribution to the history of the Chinese revolution, it also contributes to an understanding of the culture that was to be built in China after 1949."